Telling versus Counting? A Media-Archaelogical Point of View - Ernst, Wolfgang (Intermédialités / Intermediality)

(untitled) (Centre de recherche sur l'intermédialité, 2003)
There is an epistemological tension between the cultural practices of telling and counting; this tension can be seen as a function of mediatic conditions. The thesis of the following essay is a de-mystification of the digital age, a kind of media-archaeological amnesia: the numerical, which is the basis of digital technologies, has always been performed as a cultural practice of mediating reality. While story-telling has been successful on the discursive surface, an alternative way of processing the real has always been at work before it became technically materialized. To tell, after all, does not only mean “to give an account in speech or writing of events or facts”, but as well “to count things”. Rather than attempting a linear chronological trajectory, the historical relation in history between telling and counting might be described as reconfigurations according to different media.